Uji In Vitro Hidroksiapatit Berpori Yang Dilapisi Kitosan Menggunakan Larutan SBF (Simulated Body Fluid) Dengan Variasi Penambahan Kitosan - Toni Ardi; Ahmad Fadli; Silvia Reni Yenti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
One of biological method for hydroxyapatite test is in vitro test, which is testing the material outside the system or not directly on living things. Some ways include using cell culture media, test tubes or SBF (Simulated Body Fluid) solutions. This research aims to determine the effect of variations of chitosan on the results of in vitro test of porous HA coated with chitosan. This research was carried out by synthesis CaO from cockle shells followed by synthesis HA from a mixture of CaO and NH4H2PO4 using low-temperature hydrothermal method. Porous HA is made by mixing HA, potato starch and distilled water using the starch consolidation method. A coating solution is prepared by mixing 0.75%w/v and 1.50%w/v into 2%v/v 100 ml acetic acid. The porous HA is then dipped into the solution for 60 minutes then dried at room temperature for 24 hours. The sample was then immersed in a SBF (Simulated Body Fluid) solution for 28 days. Samples were then analyzed using XRD and SEM analyzes. Apatite layers were formed on the entire surface of the samples based on SEM analysis. Samples have degree of crystallinity of 86.581%-88.067% with crystal diameter of 41.220-42.340 nm. The use of more chitosan as coating reduced degree of crystallinity and crystal diameter. Keywords: chitosan, hydroxyapatite, in vitro test, SBF (Simulated Body Fluid)